Medical residents’ attitudes and emotions related to Middle East respiratory syndrome in Saudi Arabia: A cross-sectional study - Aldrees, Turki (Saudi Med J, 2017)
OBJECTIVES: To determine medical residents’ emotions, attitudes, and knowledge related to Middle East respiratory syndrome (MERS) outbreaks. METHODS: In this is a cross sectional study, self-administered questionnaires were distributed and collected before resident education activities in 4 tertiary hospitals in Riyadh, Kingdom of Saudi Arabia, between November 2015 and January 2016. The questionnaire included questions related to residents’ demographic data and their emotions, attitudes, and knowledge related to an MERS outbreak. RESULTS: Of the 228 participants analyzed, 85.5% believed their work put them at risk of infection, and two-thirds believed their family was exposed to a greater risk of infection. However, only 2.6% would change their job. Nearly half of the residents indicated that their hospital had a clear plan, and only 28% considered themselves not well prepared for an MERS outbreak. CONCLUSIONS: Our study highlights medical residents’ attitude and emotions related to MERS outbreaks. Residents’ concerns and emotions in relation to MERS should be considered in greater detail by hospital policymakers.